Foods of Poland - Sheen, Barbara (Gale virtual reference library, 2012)
Explores the foods, cooking traditions, customs, eating habits, and food sources of Poland. Topics include favorite dishes, snacks and sweets, traditional holiday meals, and the preparations and traditions associated with these foods.